Streamside detection of Chinook salmon (Oncorhynchus tshawytscha) environmental DNA with CRISPR technology - Tholen Blasko; Michael Phelps (Environmental DNA, 2024)
Abstract There is a rapidly growing interest by resource managers to utilize environmental DNA technology (eDNA) as a tool to enhance current management efforts. However, the technology remains relatively specialized, since it requires specific expertise and equipment to perform. To begin to overcome some of the obstacles restricting the widespread, routine adoption of eDNA technology, we evaluated the use of CRISPR Cas12a detection technology for in‐the‐field eDNA detection using Chinook salmon (Oncorhynchus tshawytscha) as a target species. By targeting a highly variable region in the salmonid mitochondrial DNA D‐loop, we were able to demonstrate that CRISPR Cas12a detection technology is both sensitive and specific for Chinook salmon eDNA. Engineering of the technology to work in the field was accomplished by employing rapid eDNA purification and visual readout of results using visual lateral flow or fluorescent detection methods. The technology was piloted on the fall Chinook salmon run in the Snake River of Washington State, USA, and proved to be a viable approach for streamside eDNA monitoring. With the improvement of the technology, CRISPR eDNA detection methods hold great promise in expanding the reach of eDNA as a commonly used resource management tool.